2020
DOI: 10.3233/jad-200331
|View full text |Cite
|
Sign up to set email alerts
|

The Rhythmicity of Clock Genes is Disrupted in the Choroid Plexus of the APP/PS1 Mouse Model of Alzheimer’s Disease

Abstract: Background: The choroid plexus (CP), which constitutes the blood-cerebrospinal fluid barrier, was recently identified as an important component of the circadian clock system. Objective: The fact that circadian rhythm disruption is closely associated to Alzheimer’s disease (AD) led us to investigate whether AD pathology can contribute to disturbances of the circadian clock in the CP. Methods: For this purpose, we evaluated the expression of core-clock genes at different time points, in 6- and 12-month-old femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…The circadian rhythm of CP in mouse AD is unregulated, as shown by the aberrant oscillations in the expression of clock genes. The circadian rhythmicity was recovered when a CP cell line was treated with melatonin in the presence of Aβ [ 91 ]. The same group of researchers showed the impact of circadian rhythm on the secretion of Aβ scavengers—apoliprotein J (ApoJ) and TTR—in non-transgenic rat explants, with a clear pattern of fluctuations in the expression of those proteins [ 92 ].…”
Section: Alzheimer’s Disease and The Cpmentioning
confidence: 99%
“…The circadian rhythm of CP in mouse AD is unregulated, as shown by the aberrant oscillations in the expression of clock genes. The circadian rhythmicity was recovered when a CP cell line was treated with melatonin in the presence of Aβ [ 91 ]. The same group of researchers showed the impact of circadian rhythm on the secretion of Aβ scavengers—apoliprotein J (ApoJ) and TTR—in non-transgenic rat explants, with a clear pattern of fluctuations in the expression of those proteins [ 92 ].…”
Section: Alzheimer’s Disease and The Cpmentioning
confidence: 99%
“…First, CP-related neurological impairment may be associated with loss of rhythmicity and synchronicity of CP clock genes. 108 In vitro studies of CP cells from AD mice demonstrate that there is a connection between AD and disruption to circadian rhythms within the CP. 91 , 108 This may result in a disconnect between CP and glymphatic function, resulting in sub-optimal clearance from the CSF, and increased build-up of amyloid-β and tau.…”
Section: Role Of the Choroid Plexus In Neurological Disordersmentioning
confidence: 99%
“…Intermittent administration of melatonin can reset the daily pattern of Bmal1 expression (Furtado et al, 2020). Furthermore, endogenous and exogenous melatonin ameliorates diabetes and related metabolic dysfunction by regulating insulin secretion and protecting against ROS (Espino et al, 2019).…”
Section: Melatoninmentioning
confidence: 99%
“…A study showed that melatonin treatment increased Bmal1 expression in the hippocampus, induced rapid remodeling of hippocampal neurons, and altered the synaptic structure in the CA1 and dentate gyrus regions, suggesting that melatonin can regulate the structural changes in hippocampal neurons through the circadian clock molecule Bmal1 (Ikeno & Nelson, 2015 ). Intermittent administration of melatonin can reset the daily pattern of Bmal1 expression (Furtado et al, 2020 ). Furthermore, endogenous and exogenous melatonin ameliorates diabetes and related metabolic dysfunction by regulating insulin secretion and protecting against ROS (Espino et al, 2019 ).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%